Determination Of The Best Treatment For The Tannery Industry Using Sodium Silicate (〖Na〗_2 SiO_3) With Sulfuric Acid (H_2 SO_4) (Journal of Pharmaceutical Negative Results, 2023)
The present work aims to synthesize silica sol from the acidification of sulfuric acid plus sodium silicate. Three solutions of sodium silicate were prepared at different concentrations; these were mixed with a 17% diluted sulfuric acid solution until a whitish colloidal suspension was obtained. The pH of the final solutions obtained was determined. The colloidal suspensions obtained and the gel formed were analyzed in an infrared spectrophotometer to compare the functional groups they present with those of conventional chromium salt. Finally, tanning tests were carried out with the silica sol obtained plus an aldehyde, where the typical quality parameters of leather were analyzed: dry rubbing abrasion, elongation percentage, temperature shrinkage and tensile strength. These results were compared with the data of leather tanned with chromium salts. For the comparison, statistical tests such as multiple ranges, anova, and determination of means were carried out. It is obtained as a result that the process should be carried out at room temperature up to a pH of 2.5; the infrared spectrum reveals that the functional groups of sodium silicate are similar to the chromium salts used for the tanning process. The statistical analysis shows that the silica sol obtained from a 1/5 solution of sodium silicate presents quality parameters statistically similar to those obtained from conventional chrome salt tanning.